2023
DOI: 10.1002/slct.202300174
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Molybdate Ions in Water on a Newly Synthesized Imidazolium‐based Poly (ionic liquid)

Yangui Zhao,
Yao Zhang,
Jianming Ji
et al.

Abstract: The natural biological water system has been seriously damaged due to the discharge of wastewater containing too much molybdenum, endangering the life and health of animals and plants. Imidazolium‐based poly (ionic liquid) was synthesized by grafting copolymers of styrene and 1‐(chloromethyl)‐4‐vinylbenzene into N‐methylimidazole, N‐ethylimidazole and N‐propyl imidazole, followed by characterization with the use of nuclear magnetic resonance spectrometer and Fourier transform infrared spectrometer. How the Imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the efficiency by increasing the number of steps can be related to the saturation of adsorbent sites or damage to sites active in the adsorbent. [64,65] In previous studies, [66][67][68][69][70][71][72][73][74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Adsorbents Recyclementioning
confidence: 99%